An investigation of controlling variables of riverbank erosion in sub-tropical Australia. (November 2017) - McMahon, Joseph M.; Olley, Jon M.; Brooks, Andrew P.; Smart, James C.R.; Rose, Calvin W.; Curwen, Graeme; Spencer, John; Stewart-Koster, Ben
Abstract: A large proportion of the uncertainty surrounding catchment sediment budget modelling has been attributed to sediment supplied from riverbank erosion. Some of the variables influencing riverbank erosion are bend curvature, specific streampower, riparian vegetation, and in some instances sand and gravel extraction. The empirical relationship between these variables and observed riverbank erosion across 78 km of the Upper Brisbane River, Australia was investigated. No significant relationship was found between curvature, specific streampower and riverbank erosion. The role of riparian vegetation relative to sediment supply from riverbank erosion varied with spatial location, susceptibility of a reach to erosion, and human disturbance such as sand and gravel extraction. Despite not having data on substrate type the model described approximately 37% of the variation in observed riverbank erosion. It appears that inclusion of a management practice factor in riverbank erosion models is justified, where appropriate, and may improve model performance. Highlights: Empirical relationship between variables used to model riverbank erosion at a catchment scale and observed data across 78 km investigated. No significant relationship found between river curvature, specific streampower and riverbank erosion. Role of riparian vegetation varied with spatial location, susceptibility of a reach to erosion, and human disturbance such as sand and gravel extraction. Despite not having data on substrate type the model described approximately 37% of the variation in observed riverbank erosion. Inclusion of a management practice factor in riverbank erosion models is justified, where appropriate, and may improve model performance.